Summer of Translational Aging Research for Undergraduates (STAR U): Short-term outcomes of a training program to advance diversity in aging research. - Chan, Kiana K.; Manly, Jennifer J.; Cosentino, Stephanie A.; Brickman, Adam M. (Gerontology & Geriatrics Education)
The Summer of Translational Aging Research for Undergraduates (STAR U) program, funded by the National Institute on Aging and the Alzheimer's Association, aims to enhance diversity in aging research through undergraduate education. This evaluation assesses the program's effectiveness in fostering a diverse cohort of scientists from underrepresented backgrounds. Forty-eight (96%) of 50 alumni completed a survey between April and August 2023. The survey collected demographic data, educational/career goals, program experiences, and post-program outcomes, including continued education and scientific engagement. Ninety-one percent of respondents indicated that STAR U was "extremely significant" or "very significant" in influencing them to pursue a career in science, and 93% found STAR U effective in influencing pursuits in aging research. Forty-one percent were accepted or enrolled in science-related graduate programs, with half in doctoral programs. Respondents actively disseminated their research, with 10% leading or coauthoring papers for publication. PubMed shows 22 alumni (44%) have a total of 44 publications. Qualitative feedback highlighted the program's impact on career exploration, mentorship, and the supportive environment. STAR U advances diversity in the scientific workforce focused on aging research, strengthening scholars' goals for graduate education and science careers by addressing challenges and fostering a supportive environment.